Of Priests and Kings: The Babylonian New Year Festival in the Last Age of Cuneiform Culture - Debourse, Céline, (Culture and History of the Ancient Near East., 2022)
Editing and examining source-critically for the first time the Late Babylonian ritual texts dealing with the New Year Festival, this book proposes an incisive re-interpretation of the most frequently discussed of all Mesopotamian rituals. The festival's twelve-day paradigm is dissolved in favor of a more historically dynamic model, with the ritual texts being firmly anchored in the Hellenistic period. As part of a larger group of texts constituting what can be called Late Babylonian Priestly Literature, they reflect the Babylonian priesthoods' fears and aspirations of that time much more than an actual ritual reality.